Curriculum Implementation Facilitating and Hindering Factors: The Philippines Context - Palestina, Randy L; Pangan, Agripina D; Ancho, Inero V (UPI Press, 2020)
This study focuses on the perceptions of Filipino teachers and school administrators of the different facilitating and hindering factors in curriculum implementations based on their practices and the challenges they have experienced. Using descriptive research employing quantitative design, 324 respondents were surveyed using self-made questionnaires anchored on Ecological System Theory (EST) by Bronfenbrenner (1979). The respondents from the grade school, junior high school, and senior high school expressed their agreement on the identified factors that facilitate and hinder curriculum implementation in the microsystem and chronosystem, while respondents from the college expressed their strong agreement on the two levels under the mesosystem and exosystem. At the macrosystem level, all of the respondents strongly agreed on all the items, but the highest level of agreement was evident with the respondents from the senior high school. A comparison of one-way ANOVA results revealed the respondentsâ€™ level of agreement on the facilitating and hindering factors of curriculum implementation based on the five levels of EST.Â Scrutiny on the facilitating and hindering factors in the curriculum implementation processes provides a springboard for leaders in the education sector to align programs and policies anchored on experiences and practices in the classroom along with research-based inputs.